VACUUM FLUCTUATIONS IN COSMOLOGICAL MODELS WITH COMPACTIFIED DIMENSIONS - Mkhitaryan, A. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
We study quantum effects of scalar fields in cosmological models of Friedman–Robertson–Walker with a power-low scale factor and spatial topology $R^2\time (S^l)^q$. Recurrent formulae are obtained for positive-frequency Wightman function, vacuum expectation values of the field squared and energy density.
Keywords: cosmology; vacuum fluctuations; Kaluza–Klein theories